Երկու անտիպ փաստաթուղթ՝ Խաչկավանքի եւ Կարնոյ գիւղերու ու անոնց եկեղեցիներու մասին - Մինասեան, Միհրան Ա.
This article contains the first publication of two unique documents, related to and complementing each, which refer to the demographic history and physical heritage—churches, monasteries, inscriptions, crosstones (khachk‘ars), and schools—of the Armenian-populated villages in the vicinity of Garin (Erzeroum) before and after the Genocide. The first document written in 1899 concerns Khachgavank monastery near Garin. It provides a description of the monastery and copies of a dozens of wall inscriptions․The document’s author was D. Tevekelian, who lived in Garin in 1898- 1899, and on other occasions wrote under the pseudonyms “Arshag” and “Suren”. The second document concerns the 22 villages of the Garin valley, providing brief information about each village, including the numbers of their Armenian and Turkish populations before and after the Genocide, the date when Turks settled in the village, information about the village school, church, cemeteries and nearby monasteries, etc. The detailed descriptions of the churches and the copies of their inscriptions, as well as the data about the khachkars and several manuscripts, are extremely valuable. The document was prepared during the years 1917-1918, probably by bishop Zaven Mahdesi Papaian, the emissary of the Catholicos of All Armenians in Garin and the local representative of the “Fraternal Aid Union.” It is clear from this document that less than two years after the Genocide, Turks had already managed to demolish numerous churches and monasteries in the villages of Garin. The published documents can contribute to the better recognition and study of the history and cultural heritage of the villages of the Garin valley. The documents are provided with brief introduction and references. В статье представлены два взаимосвязанных и дополняющих друг друга уникальных документа, в которых говорится о школах, церквях, монастырях, надписях, хачкарах, и т.д., армянском и другом населении деревень Карина (Эрзерум) до и после Геноцида. Первый документ был написан в 1899 году и рассказывает об историческом монастыре Хачкаванк недалеко от Карина. В документе дано описание монастыря и копии десятков настенных надписей. Автор документа - Т. Тевекелян, проживавший в Карине в 1898-1899 гг., в других случаях писавший под псевдонимами "Аршак" и "Сурен". Во втором документе даются краткие сведения о 22-х селениях Эрзерумской равнины: численность их армянского и турецкого населения до и после Геноцида, дата заселения в села турок, сведения о сельской школе, церкви, кладбище и близлежащих монастырях и т. д. Большое значение имеют подробные описания церквей и копии их настенных надписей, а также данные о хачкарах и некоторых рукописях. Документ был подготовлен в 1917-1918 годах, вероятно, епископом Завеном Махтеси Папаяном, посланником Католикоса всех армян в Карине и местным представителем «Союза братской помощи». Из документа можно заключить, что менее чем через два года после Геноцида туркам уже удалось снести многочисленные церкви и монастыри в селах Карина. Опубликованные документы могут способствовать лучшему изучению истории и культурных памятников деревень долины Карина. Документы снабжены кратким введением и примечаниями.
Keywords: Հրապարակումներ; Հայ եկեղեցւոյ պատմութիւն